КОНЦЕПТУАЛЬНІ ПІДХОДИ ДО СТВОРЕННЯ РИЗИКООРІЄНТОВАНОЇ СИСТЕМИ БЮДЖЕТНОГО КОНТРОЛЮ - Недбалюк, Ірина Романівна (Науковий журнал «Світ фінансів», 2018)
Недбалюк І. Р. Концептуальні підходи до створення ризикоорієнтованої системи бюджетного контролю.Обґрунтовано концептуальні підходи щодо створення ризикоорієнтованої системи бюджетного контролю. Визначено поняття “бюджетний ризик” та проаналізовано фактори ризику бюджетної системи залежно від стадії бюджетного процесу. Визначено складові процесу управління ризиками, що охоплює ідентифікацію, якісну й кількісну оцінку ризику, планування реагування на ризики, моніторинг і контроль ризиків. Запропоновано ризикоорієнтовану систему бюджетного контролю, яка має орієнтуватися на мінімізацію негативних наслідків виникнення ризику відповідно до зазначеної класифікації ризиків. Недбалюк И. Р. Концептуальные подходы к созданию рискоориентированной системы бюджетного контроля.Рассмотрено формирование концептуальных подходов к созданию рискоориентированной системы бюджетного контроля. Определено понятие “бюджетний риск” и проанализированы факторы риска бюджетной системы в зависимости от стадии бюджетного процесса. Определены составляющие процесса управления рисками, включающего идентификацию, качественную и количественную оценку риска, планирование реагирования на риски, мониторинг и контроль рисков. Сформирована рискоориентированная система бюджетного контроля, которая должна ориентироваться на минимизацию негативных последствий возникновения риска в соответствии с указанной выше классификацией риска. Nedbaliuk I. Conceptual approaches to creating a risk-based budget control system.Introduction. The current state of the development of the budgetary system is characterized by a number of controversial and uncoordinated moments that increase the possibility of the emergence of budgetary risks and require minimization of possible budget losses associated with the existence of budgetary risks through the formation of a risk-based budget control system.Purpose. Formulation of conceptual approaches to the creation of a risk-oriented system of budgetary control.Results. The article defines the notion of “budget risk” and analyzes the risk factors of the budget system depending on the stage of the budget process. The components of the risk management process are determined, including identification, qualitative and quantitative risk assessment, risk response planning, risk monitoring and control. A risk-based budget control system has been established, it should focus on minimizing the negative consequences of risk in accordance with the above risk classification; identification of budgetary risks at the planning stage, formation and approval, execution and analysis of the latter's results; risk assessment by qualitative and quantitative methods.Conclusions. On the basis of the definition of the concept of “fiduciary risk” and its main characteristics, it is possible to distinguish conceptual approaches to the creation of a riskoriented system of budget control, which include:– firstly, the analysis of the risk factors of the budgetary system depending on the stage of the budget process;– secondly, compliance with the risk management process, including identification, qualitative and quantitative risk assessment, risk response planning, risk monitoring and control;– thirdly, the formation of a risk-oriented system of budgetary control, which should be guided by the minimization of the negative consequences of the risk in accordance with the above classification of risk; identification of budget risks at the planning, formation and approval stage, implementation and analysis of the results of the latter; Assessing the level of risk by qualitative and quantitative methods, including monitoring and risk assessment at national and local level. Thus, the introduction of a risk-oriented system of budgetary control is not aimed at eliminating the consequences of negative external and internal influences, but to prevent their occurrence will reduce the negative consequences of violations in the system of budgetary control.